RETRACTED: Assessing vegetation productivity and environmental impact in: A remote sensing approach - Polevschvhikova Iuliia; Muminov Mahmud; Svoikin Fedor; Bozhbov Vladimir; Borozna Anatoly; Taraban Maria; Sitnikov Sergey; Ogorodnikov Sergey; Murmantseva Ekaterina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001